Helical shell models for MHD turbulence - Lessinnes, T; Carati, D (2009)
Based on the helical decomposition of both the magnetic and the velocity fields, a helical shell model for MHD turbulence is introduced. It is used to study the influence of the forcing helicity on the onset of dynamo. It is shown that the well-known GOY shell model is not well adapted for such a study and that additional interactions between the shell variables have to be taken into account.